Peningkatan Return Saham dan Kinerja Keuangan melalui Corporate Social Responsibility dan Good Corporate Governance - Eviatiwi Kusumaningtyas Sugiyanto (STIE Widya Manggala, 2011)
The purpose of this research was to find an empiric proof and analysis that stock return and financial performance of the companies could be improved through Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) at The Indonesian Capital Market. Population of this research were companies that go public at Indonesia Capital Market. Technic Sampling used purposive sampling, and found 62 companies. This companies then were divided into two categories (big and small companies) according to its total assets. And the hypotheses were tested using Structural Equation Modeling (SEM) with Partial Least Square (PLS) program. The result showed that (1) CSR had a significant positive effect towards stock return in big companies categorized, while small companies categorized had a significant negative effect of it, (2) GCG had no significant effect towards stock return in both categories, (3) Financial performance had no significant effect towards stock return in big companies categorized, but it had a positive significant effect towards it in those small, (4) CSR had a significant positive effect towards financial performance in big companies categorized, whereas in small companies it could not be found, (5) GCG had no significant effect towards financial performance in both categories, (6) as well as the GCG had no significant effect towards CSR in both categories.